Recent occurrences of opah, Lampris guttatus (Actinopterygii, Lampriformes, Lampridae), in the western Mediterranean Sea - P. Francour; M. Cottalorda J.; M. Aubert; S. Bava; M. Colombey; P. Gilles; H. Kara; P. Lelong; L. Mangialajo; R. Miniconi; P. Quignard J. (Acta Ichthyologica et Piscatoria, 2010)
The first records of Lampris guttatus in the Mediterranean Sea date back to 1807. Yet, until now it has been considered as a rare species (less than 25 specimens recorded in the literature). Since 2008, at least 23 specimens have been fished or observed along the French Mediterranean coast. In this paper, we present an updated review of records in the Mediterranean and discuss the possible link with the present sea water warming. We hypothesise that the recent Mediterranean specimens could come from the Atlantic, throughout the Gibraltar Strait, following a northward migration along the Northeast Atlantic coast due to present global warming.